COMPARATIVE METHODS OF SNOWBALL AND BRAINSTORMING ON MATERNAL KNOWLEDGE ABOUT DANGEROUS SIGNS OF PREGNANCY - Wahyuni, Sri; Maryati, Sri; Lestari, Indri Puji; Meilani, Indri (jfpublisher, 2024)
Introduction. Maternal and infant mortality in Indonesia is still quite persistent. Maternal knowledge of danger signs in pregnancy is one of the factors that can affect expectant mothers at high risk of pregnancy risk signs. Snowball is a multilevel discussion which eventually leads to consensus responses, while brainstorming begins with the group leader presenting a particular problem and then each participant responds with an opinion or feedback. The aim of this research is to find out the comparison of snowball and brainstorming methods on maternal knowledge about the danger signs of pregnant women. Method. This research uses a quasi-experimental design with a one-group design that is pre-tested and post-tested using the Snowball method and Brain Storming group. The population was 45 expectant mothers who made antenatal visits. The samples consisted of 26 expectant mothers who were selected by purposive sampling. Data was collected using a questionnaire and analyzed by Marginal Homogeneity test. Result & Analysis. Before the health promotion, most respondents in the brainstorming group had sufficient knowledge (61.5%) and those with insufficient knowledge amounted to 38.5%. After being trained with the brainstorming method, respondents' knowledge increased to 53.8% with good knowledge, 38.5% with fair knowledge, and 7.7% with insufficient knowledge (p value 0.008). Meanwhile, 92.3% of the respondents' knowledge was insufficient and 7.7% of the respondents' knowledge was adequate (p value 0.008). However, after the health promotion, the respondents' knowledge changed to 46.1% moderately knowledgeable, 38.5% less knowledgeable, and 15.4% well knowledgeable (p value 0.013). Discussion. There is a significant difference in the knowledge of pregnant women before and after being promoted with the brainstorming and snowball methods. It is expected that the brainstorming health promotion method can be applied as one of the methods in improving the knowledge of pregnant women.